Capital structure and firm performance: Evidence from listed companies in China - LI, QINYI (2022)
The firm performance of capital institutions and corporations has been a matter of intense interest for researchers in finance. The economic market has witnessed sluggish global economic growth. China's economy has had to adapt by shifting from an investment-driven model to one driven by industrial upgrading and technological innovation. Consistent with the globalization of economic policy and financial markets, the profusion of investment and financing alternatives in the current economic climate is increasing the reliance of corporations on the capital markets. Capital is necessary to expand into new enterprises and for corporate growth. A company's performance is a direct reflection of its firm performance; consequently, a solid capital structure is essential to enhancing a company's performance and contributing to its sustainable growth.